2017
DOI: 10.1186/s12889-017-4859-6
|View full text |Cite
|
Sign up to set email alerts
|

Canadian 24-Hour Movement Guidelines for the Early Years (0–4 years): An Integration of Physical Activity, Sedentary Behaviour, and Sleep

Abstract: BackgroundThe Canadian Society for Exercise Physiology convened representatives of national organizations, research experts, methodologists, stakeholders, and end-users who followed rigorous and transparent guideline development procedures to create the Canadian 24-Hour Movement Guidelines for the Early Years (0–4 years): An Integration of Physical Activity, Sedentary Behaviour, and Sleep. These novel guidelines for children of the early years embrace the natural and intuitive integration of movement behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
404
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(461 citation statements)
references
References 63 publications
10
404
2
14
Order By: Relevance
“…Meanwhile, sedentary behaviour is prevalent and pervasive in modern society, and data from adults in high‐income countries suggest that most time awake is spent being sedentary . Currently, the United States and other high‐income countries have mainly focused on physical activity promotion and have issued health guidelines, but few guidelines exist for sedentary behaviour . This absence represents an important gap in public health guidelines because of the severe consequences and profound burden of total sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, sedentary behaviour is prevalent and pervasive in modern society, and data from adults in high‐income countries suggest that most time awake is spent being sedentary . Currently, the United States and other high‐income countries have mainly focused on physical activity promotion and have issued health guidelines, but few guidelines exist for sedentary behaviour . This absence represents an important gap in public health guidelines because of the severe consequences and profound burden of total sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that young children's objectively assessed physical activity may be as low as 4% of the day . Assuming a 13‐h waking day for a young child , this falls below the guideline of 180 min of light, moderate or vigorous‐intensity physical activity (LMVPA) per day recommended by government bodies internationally .…”
Section: Introductionmentioning
confidence: 95%
“…For instance, guideline recommendations suggest that children aged 3‐5 years of age should be doing at least 180 min of physical activity per day, which should include 60 min of moderate and vigorous physical activity (MVPA) (Okely et al, ; Tremblay et al, ). The inclusion of 60 min of MVPA in the most recent guidelines was driven by findings that physical activity performed at a light intensity was not associated with a range of health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence suggests that preschool children in South Africa are highly active (Draper et al, ; Jones, Hendricks, & Draper, ), and have adequate gross motor skills (Draper, Achmat, Forbes, & Lambert, ; Draper et al, ). These studies, mostly from low‐income settings, have reported that South African preschoolers are not only meeting the guidelines for physical activity (Okely et al, ; Tremblay et al, ), but are exceeding them – with some children accumulating more than 400 min of total physical activity and over 100 min of MVPA per day. This is a very different context to those from which the majority of physical‐cognitive findings are derived, in which habitual physical activity levels are substantially lower (Beets, Bornstein, Dowda, & Pate, ; Hinkley, Salmon, Okely, Crawford, & Hesketh, ; Tucker, ).…”
Section: Introductionmentioning
confidence: 99%